Camões and the Erotic Dream of Luís Rafael Soyé - Teixeira, Gil Clemente (Revista Desassossego, 2023)
Luís Rafael Soyé (1760-1831), an author whose biography takes place in cities as different as Madrid, Lisbon, Paris, and Rio de Janeiro, published his first book in Lisbon in 1786: Dream, erotic poem, which he offered to the beneficent prince of Brazil, D. José. In this poem, we find peculiar traits of his work: a desire to renew the Portuguese poetry, an extreme care with language, a broad dialogue with the European literary tradition. If we look at the universe of Soyé’s poetry, we easily find the constellation Camões. Thus, we intend to show how the poetry of Camões is received/rewritten in his first literary adventure.